Madrasah Head Leadership Strategy in Improving the Quality of Islamic Education in the Madrasah Ibtidaiyah Negeri Fakfak - Djoyo, Rachmawati; Hamzah; Amin, Surahman (LPPM IAIN Sorong, 2024)
This research uses qualitative field study research to analyze the leadership, strategies, and impact of madrasa head leadership in improving the quality of Islamic education located at MIN Fakfak. Data was collected through observation, interviews, and documentation. Data analysis in this research is data reduction, data presentation, and conclusion. The results show that:The leadership of the Madrasah Principal at MIN Fakfak applies a participative leadership approach, has a democratic, straightforward, and open leadership style, prepares time to communicate with student teachers and school residents, emphasizes teachers and school residents to fulfill the norms learning norms with high discipline, monitoring students' learning progress, holding meetings actively, regularly and continuously with the school committee, teachers and school community, guiding and directing teachers in solving problems and being willing to assist proportionally and professionally, allocating the necessary funds to guarantee the implementation of learning programs, conduct class visits to observe learning activities.The leadership strategy of the Madrasah head in improving the quality of Islamic education at MIN Fakfak, quality educational input, and an effective learning process, can produce the output expected by the school.The impact of the Madrasah head's leadership strategy on improving the quality of Islamic education at MIN Fakfak can be seen from the impact on input, process, and output where the quality of education is getting higher.